2020
DOI: 10.1029/2020jd032604
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Nitrate Aerosol Formation Pathways in a Southeast Chinese City by Dual Isotope and Modeling Studies

Abstract: Nitrate (NO3−), one of the most important inorganic aerosols in the atmosphere, is mainly formed by oxidation of NOx by the hydroxyl radical (OH) and ozone (O3) in urban atmospheres. However, the fractional contributions of its various oxidation pathways remain unclear. Here, we collected particulate matter with aerodynamic diameter less than 2.5 μm (PM2.5) samples in a second‐tier city in southeast China from 1 September to 31 December 2017 and measured the NO3− and nitrate isotopic compositions (δ15N and δ18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The average contributions of the •OH pathway in summer and winter were 61.8 ± 18.3% and 36.3 ± 20.6%, respectively. This indicates a transition of the dominant pathway of NO 3 − formation from the •OH pathway in summer to the O 3 pathway in winter (Xiao et al., 2020). The contribution of the •OH pathway was largest in the summer of 2017 (73.56 ± 13.24%), and smallest in the winter of 2017 (26.54 ± 13.63%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average contributions of the •OH pathway in summer and winter were 61.8 ± 18.3% and 36.3 ± 20.6%, respectively. This indicates a transition of the dominant pathway of NO 3 − formation from the •OH pathway in summer to the O 3 pathway in winter (Xiao et al., 2020). The contribution of the •OH pathway was largest in the summer of 2017 (73.56 ± 13.24%), and smallest in the winter of 2017 (26.54 ± 13.63%).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the formation pathways of NO 3 − in the atmosphere are relatively complicated (R 1 –R 12 ), but the main ones are the O 3 and •OH pathways (Zong et al., 2017). Studies have shown that the processes of NO converting into NO 2 through HO 2 or ROO (R 4 –R 5 ) and the HC pathway (R 8 , generally <5%) are limited (Alexander et al., 2020; Xiao et al., 2020), so they were ignored in this study. From 2014 to 2019, δ 18 O–NO 3 − oscillated in summer, with increases seen in winter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that the oxidation of NO 2 by •OH (•OH + NO 2 ) in the gas phase and the hydrolysis of N 2 O 5 on pre-existing aerosols (N 2 O 5 +H 2 O, heterogeneous process) were considered to be the two main reactions controlling the formation of NO 3 − (Morin et al, 2009;Xiao et al, 2020). The conversion process of NO to NO 2 mainly includes O 3 oxidation and peroxy radical (HO 2 and its organic homolog RO 2 ) oxidation.…”
Section: Source and Conversion Of Nitrate Based On N And O Isotopic S...mentioning
confidence: 99%
“…As a substantial component of ambient particulate matter, nitrate (NO 3 − ) has an important impact on air quality, climate change, radiative heat budget, and biogeochemical cycling of reactive nitrogen (Ipcc, 2013;Liu et al, 2013;Altieri et al, 2021). According to data from the global air quality monitoring website AirVisual in 2017, Asia is home to 20 cities with the worst air pollution in the world, and NO 3 − was an important contributing factor to particulate matter haze formation in cities (Ding et al, 2017;Xiao et al, 2020;Guo et al, 2021). In addition, as the precursor of NO 3 − , the total NO x emissions in China have exceeded 1.5 million tons per year in the past 10 years, approaching or exceeding the upper limits of the environmental carrying capacity (Fang et al, 2011;Rollins et al, 2012;Azimi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sulfate forms primarily through atmospheric oxidation of SO 2 emitted mainly from coal burning, while nitrate originates from NO x from vehicle exhaust and power plants (Huang et al, 2014; Wang et al, 2014). The secondary generation of organic aerosols is more challenging due to complex precursors and formation mechanisms (Sun et al, 2014; Xu et al, 2016; Xiao et al, 2020). The daytime nitrate and sulfate were mainly from photochemistry while heterogeneous hydrolysis of N 2 O 5 dominates the formation of nitrate and efficient heterogeneous reaction generated sulfate during nighttime (Li, Jacob, et al, 2019; Tian et al, 2019; Ye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%